Executive Committee Minutes 2010-02-04 - Academic Senate:::::::::
New Minor in Electrical Engineering approved for Senate consent calendar. FSAC Response to Staff Report on Faculty/Staff Civility approved as information item at the Senate. Continued discussion on Double Majors and campus authority to graduate students. Request for re-creation of technology subcommittee of EPC. Faculty Eligible for Emeritus Status approved for Senate consent calendar.